A Generic Study on Diabetic Retinopathy Detection (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Diabetic Retinopathy is one of a major cause of visual defects in the growing population which affects the light perception part of the retina. It affects both types of diabetes mellitus. It occurs when high blood sugar levels damage the blood vessels in retina causing them to swell and leak or stop blood flow through them. It starts with no or mild vision problems and can eventually cause blindness if not treated.With the advancements in technology, automated detection and analysis of the stage of Diabetic Retinopathy will help in early detection and treatment. Almost 75% of the patients with diabetes have the risk of being affected by this disease. With early detection this disease can be prevented. Currently DR detection is a traditional and manual, time-consuming process. It requires a trained technician to analyze the color fundus image of retina.With the ever growing population, DR detection is very high in demand to prevent blindness. In this paper we aim to review the existing methodologies and techniques for detection. Also a system for the detection of the 4 stages of DR is proposed.